Synthesis of P‐stereogenic macrocycles. Issue 1 (19th December 2016) - Kato, Ryosuke; Fukuyama, Misuzu; Morisaki, Yasuhiro; Chujo, Yoshiki
Abstract: Optically active macrocycles consisting of two P‐stereogenic bisphosphine units and two π‐conjugated linkers were synthesized via [2 + 2] cyclization. A clear Cotton effect was observed in the π–π* transition region of the π‐conjugated units, indicating that the chirality is induced by the P‐stereogenic bisphosphine moieties onto the π‐conjugated linkers. Compared with model compounds, the orientation of the two π‐conjugated units was essential to the induced circular dichroism. Macrocycles containing extended π‐conjugated linkers exhibited large molar extinction coefficients, high photoluminescence quantum efficiencies, and intense circularly polarized luminescence with the large dissymmetry factors.